The effect of NBI on UWB time-hopping systems. - Xiaoli Chu
This letter presents an analysis of the effect of narrowband interference (NBI) on ultrawideband (UWB) time-hopping (TH) systems in the presence of multipath fading using both analytical derivations and simulations. Our analysis demonstrates that NBI may be an issue in some instances. In addition, we suggest three NBI suppression schemes for combating NBI in UWB TH systems. Single-link performance of these schemes in conjunction with a Rake-type receiver structure is estimated for both the ideal all-Rake receiver and the simpler partial-Rake receiver in an indoor environment. Two UWB pulse shapes that meet the Federal Communications Commission rules for UWB communications are considered in the investigation.
Keywords: MMSE; Rake-type receiver; UWB time-hopping systems; Binary pulse position modulation; Frequency-domain notch filtering; Indoor environment; Minimum mean square error combining; Multipath fading; Narrowband interference; Single-link performance; Time-domain modulation parameter; Ultra wideband system